Riddick - Twohy, David; Diesel, Vin; Urban, Karl, 1972-; Sackhoff, Katee (Universal City, CA : Universal Studios Home Entertainment, 2014)
After being left for dead, Riddick finds himself fighting against alien predators.
Originally released as a motion picture in 2013.
Sequel to "The chronicles of Riddick" (2004).
Dolby digital 5.1, wide screen 2.40:1.
Features: Vin's Riddick, Meet the Mercs, Riddick : blindsided.
Vin Diesel, Karl Urban, Katee Sackhoff, Jordi Mollà, Matt Nable.
MPAA rating: R.
Keywords: Human-alien encounters -- Drama; Good and evil -- Drama; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Feature films; Science fiction films